Intellectual, scientific, and educational influences on sustainability research - Turvey, Rose A. (Rose Adapon), 1952-; Kurissery, Sreekumari, 1961- (Practice, progress, and proficiency in sustainability (PPPS) book series., 2019)
"This book focuses on intellectual, scientific and educational influences on sustainability research. It offers the latest insights into the global research landscape underpinning the science of sustainability. It also contains an international, interdisciplinary, transdisciplinary and cross-sector collaboration in the science of sustainability"--